Dyeing Properties of Vilangin Synthesized from Embelin on Cotton Fibre - Koske, Margaret; Kiprop, Ambrose K.; Chepkwony, Sarah C.; K’Owino, Isaac O. (European Journal of Applied Sciences, 2021)
Semi synthesis involves the use of chemical compounds isolated from natural sources as the starting materials to produce other distinct compounds with added value and improved chemical properties. Most modified dyes have been synthesized through chemical modification to increase solubility and fastness properties of the dyes. A semi-synthetic dye (vilangin) has been obtained through chemical modification of embelin (a benzoquinone) isolated from Embelia schimperi berries crude extract, a plant-based dye. The vilangin dye was synthesized by condensation of embelin with formaldehyde in acetic acid solution., Their melting point and thin layer chromatography was done to determine purity. Characterization was done using Ultraviolet–Visible spectroscopy, Fourier Transform Infrared spectroscopy, Liquid chromatography Mass spectrometry and Nuclear Magnetic Resonance Spectroscopy. Embelin and the semi- synthesized dye were applied on cotton fabrics and colour fastness properties such as wash fastness, rubbing fastness, light fastness were evaluated. Embelin dye and vilangin dye exhibited similar colour strengths (K/S values) of 0.18 and 0.19 respectively. Use of mordants increased the colour strengths from 0.19 to 0.23 for the pre-mordanted cotton fibers ,the post-mordanted were in the range of 0.19-0.32 whereas the simultaneous mordanting showed better characteristics in the range of 0.27-0.52 for the vilangin dye. It has thus been established that the semi-synthetic dye possessed superior fastness properties compared to the parent embelin dye.